Cytomegalovirus uveitis in HIV-infected patients: course and outcomes - T. D. Sizova; V. M. Khokkanen; D. A. Gusev; E. V. Boyko (Журнал инфектологии, 2020)
Cytomegalovirus uveitis is one of the AIDS marker diseases, develops with severe immunodeficiency and is the main cause of blindness in HIV-infected patients.The aim of our work is to study the course and outcomes of CMV uveitis in patients with HIV infection over the past 10 years.Materials and methods. The study was conducted at the St. Petersburg Center for the Prevention and Control of AIDS and Infectious Diseases and at the Department of Ophthalmology of North-Western State Medical University named after I.I. Mechnikov. The analysis of statistical data of HIV Newsletters in St. Petersburg for 2009-2019 was carried out, as well as the Journal of Ophthalmologist Examination of the AIDS Center to assess the long-term dynamics of detection of CMV uveitis, CMV associated retinal detachment, and cases of vision loss.Results. On average, CMV eye damage occurred in 1.65% of patients. In most cases, the involvement of the retina was predominantly peripheral (50-89%). Neuritis, panuveitis, cystic macular edema and retinal detachment were also registered. A positive strong linear relationship was found between the number of new cases of HIV infection already detected in the AIDS stage and new cases of cytomegalovirus damage to the organ of vision. There is a very strong inverse linear relationship between the frequency of detection of CMV uveitis and the amount of antiretroviral therapy provided.Conclusion. Conducting antiretroviral therapy and providing it to an increasing number of patients helps to reduce the incidence of HIV infection in St. Petersburg and probably secondary CMV infection with damage to the organ of vision.